AKTUALISASI SISTEM PELEMPAR BOLA PADA ROBOT ISOLA_229 - Nabawi A.M., Ridha; R. Aam Hamdani; Asep Hadian Sasmita (Jurnal Permadi : Perancangan, Manufaktur, Material dan Energi, 2020)
The ISOLA_229 robot is designed to have a maximum dimension of a cube of 1 m3 with an extension of up to 1.8m, must be able to throw the ball in 3 throwing zones that have different shooting distances and heights according to the rules of the ABU Robocon robot contest with the theme "Throwing the blessing ball", a traditional game from Vietnam. The ISOLA_229 robot that has been made meets the dimensions, but throws the ball not yet able to reach the target in the shooting zone 3. There is a need for analysis to find out the cause of the problem and how to solve the problem, one of which is descriptive method. The analysis carried out on the ISOLA_229 robot focused on the problem of the ball throwing system. The results of the analysis of the ISOLA_229 robot ball throwing system found that it was necessary to reduce the throwing speed by 65% ​​from normal speed at air pressure P = 6 bar and change the elevation angle from = 45o to = 50o to reach the target in throwing zone 3.